The Right to a Happy Death for the Navy’s Elderly - Sutarno Sutarno; Adriano Adriano (Hang Tuah Law Journal, 2022)
Everyone wants to live happily in their life, including in the final moments of their life. It’s also the same for the retired personnel of the Indonesian Navy. There are many efforts to make a happy life, especially while they’re still active in their Job. One of the slogans to encourage life is Old Navy Never Die. This study analyzes the legislation of near-death elderly of retired Indonesian Navy that has a slogan Old Navy Never Die. Legislation of near-death is usually related to euthanasia or palliative care, especially to avoid prolonged suffering. The method of this study is juridical normative through statute and conceptual approach, reinforced with a limited empirical approach through limited interviewa. The result found in this study is there is no specific legislation about the legislation of near-death elderly in retired Indonesian Navy. The condition and the legislation for the elderly Indonesian Navy are the same as another Indonesian netizen. The slogan is only used to encourage the soldier to be a real seaman. In Indonesia, all the netizens, there is a tendency to allow passive euthanasia, in addition to street palliative care in place. The suggestion is to make strong legislation concerning palliative care and strong legislation for retired elderly naval care center of the naval base.